Taxonomic Status and Phylogenetic Relationship of the Charadriidae Family Based on Complete Mitogenomes - Qian, Weiya; Liu, Yizheng; Miao, Keer; Chang, Qing; Hu, Chaochao (Current genomics, 2023)
Background: The Charadriiformes provide a good source for researching evolution owing to their diverse distribution, behavior, morphology, and ecology. However, in the Charadrii, family-level relationships remain understudied, and the monophyly of Charadriidae is also a subject of controversy. Methods: In the present study, we generated complete mitogenomes for two species, Charadrius leschenaultii and Charadrius mongolus , which were found to be 16,905 bp and 16,844 bp in length, respectively. Among the 13 protein codon genes, we observed variation in the rate of nonsynonymous substitution rates, with the slowest rate found in COI and the fastest rate observed in ATP8. The Ka/Ks ratio for all Charadriidae species was significantly lower than one, which inferred that the protein-coding genes underwent purifying selection. Results: Phylogenetic analysis based on the genes of Cyt b , 12S and ND2 revealed that the genus Pluvialis is the sister group of three families (Haematopodidae, Ibidorhynchidae, Recurvirostridae). However, the phylogenetic analysis based on complete mitogenomes indicated that the genus Pluvialis is within the Charadriidae family. Conclusion: This study highlights the importance of carefully selecting the number of genes used to obtain accurate estimates of the species tree. It also suggests that relying on partial mtDNA genes with fast-evolving rates may lead to misleading results when resolving the Pluvialis sister group. Future research should focus on sequencing more mitogenomes at different taxonomic levels to gain a better understanding of the features and phylogenetic relationships within the Charadriiformes order.